Serum high-density lipoprotein is associated with better cognitive function in a cross-sectional study of aging women - Bates, K.; Sohrabi, H.; Rainey-Smith, S.; Weinborn, M.; Bucks, R.; Rodrigues, M.; Beilby, J.; Howard, M.; Taddei, K.; Martins, G.; Paton, A.; Shah, T.; et al. (2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Purpose/Aim of the study: Poor cardiovascular health, including obesity and altered lipid profiles at mid-life, are linked to increased risk of Alzheimer's disease (AD). The biological mechanisms linking cardiovascular health and cognitive function are unclear though are likely to be multifactorial. This study examined the association between various lipoproteins and cognitive functioning in ageing women. Materials and Methods: We investigated the relationship between readily available biomarkers (i.e. serum lipoprotein) and cognitive decline in domains associated with increased risk of AD (e.g. episodic verbal memory performance and subjective memory complaint). We report cross-sectional data investigating the relationship between serum total cholesterol, triglycerides, high-density lipoprotein (HDL-C) and low-density lipoprotein with verbal memory and learning ability in 130 women with and without memory complaints (n = 71 and 59, respectively) drawn from a study investigating cognitively healthy Western Australians (average age 62.5 years old). Results: After statistical modelling that controlled for the effects of age, depression and apolipoprotein E genotype, HDL-C was significantly associated with better verbal learning and memory performance, specifically short and long delay-free recalls (F = 3.062; p < .05 and F = 3.2670; p < .05, respectively). Conclusion: Our cross-sectional findings suggest that the positive effect of HDL-C on verbal memory may be present much earlier than previously reported and provide further support for the role of HDL-C in healthy brain ageing. Further exploration of the protective effect of HDL-C on cognitive function in ageing is warranted through follow-up, longitudinal studies.